2020
DOI: 10.1002/jnr.24549
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of age‐related hearing loss

Abstract: Age‐related hearing loss (ARHL) has recently been confirmed as a common complex trait, that is, it is heritable with many genetic variants each contributing a small amount of risk, as well as environmental determinants. Historically, attempts to identify the genetic variants underlying the ARHL have been of limited success, relying on the selection of candidate genes based on the limited knowledge of the pathophysiology of the condition, and linkage studies in samples comprising related individuals. More recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…By contrast, age-related sensorineural hearing loss (ARSHL) is extremely common, affecting around 40% of adults over 60 years old ( Hoffman et al., 2017 ). Our understanding of the genetics of ARSHL lags behind that of prelingual hearing loss ( Wells et al., 2020 ). Prior family studies have shown that HTs are heritable, or correlated among biological relatives, suggesting that there is a sizable genetic component to ARSHL ( Duan et al., 2019 ; Hendrickx et al., 2013 ; Kvestad et al., 2012 ; Raynor et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, age-related sensorineural hearing loss (ARSHL) is extremely common, affecting around 40% of adults over 60 years old ( Hoffman et al., 2017 ). Our understanding of the genetics of ARSHL lags behind that of prelingual hearing loss ( Wells et al., 2020 ). Prior family studies have shown that HTs are heritable, or correlated among biological relatives, suggesting that there is a sizable genetic component to ARSHL ( Duan et al., 2019 ; Hendrickx et al., 2013 ; Kvestad et al., 2012 ; Raynor et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of EYA4 variants to hearing loss has been well established. 55 HOMER2 is involved in intracellular homeostasis of calcium and cytoskeletal organization and has been previously associated with hearing loss, 56 but its function within the stria vascularis remains unknown. TMPRSS9 encodes a membrane-bound serine polyprotease involved in the proliferation of inner ear progenitor cells in the mouse cochlea.…”
Section: Gtex Tissue Enrichment Analysis and Cell-type Specificity Of...mentioning
confidence: 99%
“…For families with hearing loss variants, knowing the specific sequences underlying their hearing loss allows medical providers to predict if their hearing loss is part of a syndrome that may lead to further comorbidities, including heart [ 19 ], thyroid [ 20 ], or visual dysfunction [ 21 ]. Genetic variants may also potentiate hearing loss from noise damage [ 22 ], drug damage [ 23 ], or aging [ 24 ]. It is important to note that even within families, the same genetic variants can lead to hearing loss on different time scales and to differing extents, likely due to the presence of genetic or environmental modifiers.…”
Section: Causes Of Sensorineural Hearing Lossmentioning
confidence: 99%